The effect of fossil fuel and hydropower on carbon dioxide emissions: EKC validation with structural breaks - Xia, Chenxia; Wang, Zilong (Journal of Environmental Engineering and Landscape Management, 2020)
This research is carried out to explore the relationship between economic growth, fossil energy, carbon emissions, hydropower, industrial development and energy endowment, and the effectiveness of the environmental Kuznets curve (EKC) hypothesis in China from 1965 to 2016 is tested. To this end, some econometric methods with structural breaks are employed. The results illustrate that the EKC considering structural breaks is existed in China. Furthermore, hydropower consumption can significantly reduce carbon dioxide (CO2) emissions, however, the reduction can be masked by the increase of fossil energy consumption. In addition, industrialization level and economic growth positively and significantly affect CO2 emissions. Finally, some policies for reducing CO2 emissions are put forward.